Association of body mass index, cardiorespiratory fitness, and theirs correlates among female physical therapy students in Multan - Perwasha, Perwasha; khan, Imran Ahmad; Kanwal, Noshaba; Gul-E- Mizgan; Khalid Khan, Maliha; Iram Batool, Hafiza (Journal of the Pakistan Medical Association, 2021)
Objective: To explore the correlates directly associated with body mass index and cardiorespiratory fitness among undergraduate female physiotherapists. Methods: The cross-sectional study was conducted from October to December 2020 at Ali-Ul-Murtaza Department of Rehabilitation Sciences, Muhammad Institute of Medical and Allied Sciences, Multan, Pakistan, and comprised undergraduate female physiotherapists aged17-25 years. The subjects were assessed on the basis of Physical Activity Readiness Questioner, body mass index and standard criteria of cardiorespiratory fitness. Data was analysed using SPSS 20. ------ Continue